Tasting God: Martin Buber's Sweet Sacrament of Dialogue - Kramer, Kenneth (Horizons, 2010)
Martin Buber (1878-1965) stands among the most significant philosophers of the twentieth century. While many studies have attempted to summarize the scope of Buber's writings, here I will highlight some key implications of Buber's basic insight that there exists a deeply reciprocal bond between genuine interhuman dialogue and the divine-human relationship. Buber characterized authentic dialogue as sacramental, and he suggested that it included four elemental aspects: turning, addressing, listening, and responding. Every genuine dialogue opens out toward transcendence insofar as God's presence can be glimpsed as "absolute Person," can be tasted as the spirit of elemental togetherness. The fundamental result of engaging in sacramental dialogue, both with others and with God, both in public discourse and private prayer, is the renewal of the entire person. As Buber repeatedly described it, to become who we are created to be—dialogical partners with God—it is the responsibility of every person to participate in God's creative, revealing, and redemptive presence in that part of the world where we stand.